Hubungan Aktivitas Fisik Degan Status Gizi Pada Ibu Hamil - Resy Haryanti (Jurnal Medika Hutama, 2021)
Nutritional is very important to be considered during pregnancy . This study aims to determine the cif good nutrition durig pregnancy eats the fetus. As well as the level of physical activity during pregnancy is also considered during pregnancy pregnant women belance the level of physical activity with nutritional so that the nutrional status during pregnancy is good. This study aims determine of pyhsical activity with nutrional status in pregnant women at the Simpang Tiga inpatient Health center in Pekanbaru. This type of research is quantitative with a descriptive correlation method and cross sectional desaign. The sample in this study amounted to 95 respondents pregnant women at the Spang Tiga Inpatient Health Center in Pekanbaru. The instrument of this study wa to use the Beacke questionnaire on the level of physical activity with nutrional status in pregnant women. The analysis method is an alternative test that is Kolmogorow Smirnov test. There is no correlation between physical activity and nutrional status of pregnant womwn at the Simpang Tiga with pvalve > 0,05 = o,893. The results of thes study there relationship between physical activity and nutrional status in pregnan women. Becaos nutrional intake with fission activity of pregnant womwn is belanced, as well as other fectors such as age, weigth, habits and aconomic status of the mother is good and pregnant womwn still need to pay attention to nutritional in accordance with the level of physical activity affecs energy needs, where energy is obtained from meanig